2022
DOI: 10.3389/fimmu.2022.995235
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal administration of a single dose of MVA-based vaccine candidates against COVID-19 induced local and systemic immune responses and protects mice from a lethal SARS-CoV-2 infection

Abstract: Current coronavirus disease-19 (COVID-19) vaccines are administered by the intramuscular route, but this vaccine administration failed to prevent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus infection in the upper respiratory tract, mainly due to the absence of virus-specific mucosal immune responses. It is hypothesized that intranasal (IN) vaccination could induce both mucosal and systemic immune responses that blocked SARS-CoV-2 transmission and COVID-19 progression. Here, we evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(63 citation statements)
references
References 69 publications
2
57
0
4
Order By: Relevance
“…The viral control was observed in the absence of neutralizing antibodies, and it was linked to the induction of specific CD8+ T cell responses (183). Finally, intranasal immunization has been shown to provide protection against VoCs in animal models (243,244). These data highlight both the protective value of SARS-CoV-2-specific T cells resident in the upper respiratory tract and the effective nextgeneration COVID-19 intranasal vaccine approach to induce mucosal immunity against current and future VoCs, which could be a promising strategy to reduce breakthrough infections and curb SARS-CoV-2 transmission.…”
Section: Hybrid Immunity Against Sars-cov-2mentioning
confidence: 97%
“…The viral control was observed in the absence of neutralizing antibodies, and it was linked to the induction of specific CD8+ T cell responses (183). Finally, intranasal immunization has been shown to provide protection against VoCs in animal models (243,244). These data highlight both the protective value of SARS-CoV-2-specific T cells resident in the upper respiratory tract and the effective nextgeneration COVID-19 intranasal vaccine approach to induce mucosal immunity against current and future VoCs, which could be a promising strategy to reduce breakthrough infections and curb SARS-CoV-2 transmission.…”
Section: Hybrid Immunity Against Sars-cov-2mentioning
confidence: 97%
“…Recently, a diversity of animal experiments and clinical trials are ongoing to evaluate the immune responses and the safety and efficacy of intranasal administration of COVID-19 vaccines, respectively. 220 It is hypothesized that intranasal vaccination may induce both mucosal and systemic immune responses, 221 and thus the…”
Section: Covid-19 Vaccinesmentioning
confidence: 99%
“…It is hypothesized that intranasal vaccination may induce both mucosal and systemic immune responses, 221 and thus the local mucosal immunity may prevent the virus infection through the upper respiratory tract and block transmission to other people 222 . In mice, intranasal administration of virus‐based vaccine candidates expression SARS‐CoV‐2 spike protein elicited robust specific IgG and IgA antibodies and polyfunctional S‐specific Th1‐skewed CD4 + and cytotoxic CD8 + T‐cell immune responses 221 . Four COVID‐19 mucosal vaccines have been approved as booster for the prevention of COVID‐19 infection in China, Russia, India and Iran 222 .…”
Section: Covid‐19 Vaccinesmentioning
confidence: 99%
“…We and others described animal studies supporting use of the host-range restricted vaccinia virus Ankara (MVA) as an alternative vector for COVID-19 vaccines 1216 . Recent animal studies demonstrated advantages of IN delivery of recombinant MVAs (rMVAs) expressing S 1719 . Anti-SARS-CoV-2 IgA and IgG as well as specific T cells were detected in the lungs of IN vaccinated mice and virus was diminished in the upper and lower respiratory tracts following challenge of K18-hACE2 mice with SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…We and others described animal studies supporting use of the host-range restricted vaccinia virus Ankara (MVA) as an alternative vector for COVID-19 vaccines [12][13][14][15][16] . Recent animal studies demonstrated advantages of IN delivery of recombinant MVAs (rMVAs) expressing S [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%